Investigation of structure and photocatalytic activity on TiO2 hybridized with graphene: compared to CNT case1. Issue 79 (28th August 2015) - Guo, ShuaiNan; Fan, JinChen; Xu, QunJie; Min, YuLin
<x xml:space="preserve">Abstract</x> The structures of TiO2 hybridized with graphene by three different method were studied and their corresponding photocatalytic activities was compared by degrading RhB under UV and visible light irradiation.